Assessing capacity for health policy and systems research in low and middle income countries* - Mills Anne; Gonzalez Block Miguel A (BMC, 2003)
Abstract Background As demand grows for health policies based on evidence, questions exist as to the capacity of developing countries to produce the health policy and systems research (HPSR) required to meet this challenge. Methods A postal/web survey of 176 HPSR producer institutions in developing countries assessed institutional structure, capacity, critical mass, knowledge production processes and stakeholder engagement. Data were projected to an estimated population of 649 institutions. Results HPSR producers are mostly small public institutions/units with an average of 3 projects, 8 researchers and a project portfolio worth $155,226. Experience, attainment of critical mass and stakeholder engagement are low, with only 19% of researchers at PhD level, although researchers in key disciplines are well represented and better qualified. Research capacity and funding are similar across income regions, although inequalities are apparent. Only 7% of projects are funded at $100,000 or more, but they account for 54% of total funding. International sources and national governments account for 69% and 26% of direct project funding, respectively. A large proportion of international funds available for HPSR in support of developing countries are either not spent or spent through developed country institutions. Conclusions HPSR producers need to increase their capacity and critical mass to engage effectively in policy development and to absorb a larger volume of resources. The relationship between funding and critical mass needs further research to identify the best funding support, incentives and capacity strengthening approaches. Support should be provided to network institutions, concentrate resources and to attract funding.